2019
DOI: 10.17810/2015.93
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Teachers’ Continuous Professional Development and Its Impact on Educational Quality: Primary Schools in Fagita Lekoma Woreda, Awi Zone, Amhara Region, Ethiopia in Focus

Abstract: This study examined the extent to which Primary Schools of Fagita Lekoma Woreda implement teachers’ CPD and its impact to quality in education. Data were collected from teachers, school principals, and woreda education office supervisors. Questionnaire and interview were used as the data gathering tools of the study. The quantitative data was analyzed using percentage and one sample t-test. The qualitative data was analyzed via thematic description. The findings confirmed that the respondents’ level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 5 publications
2
9
0
1
Order By: Relevance
“…In the same way, CPD affected primary schools of Scottish regarding group work practices (Thurston, Christie, Howe, Tolmie, & Topping, 2008). The previous studies regarding CPD had a positive and significant impact on the quality education of primary schools of Ethiopia (Melesse & Gulie, 2019). These findings also are in support of different researchers like (Feiman-Nemser, Schwille, Carver, & Yusko, 1999).…”
Section: Discussionsupporting
confidence: 68%
“…In the same way, CPD affected primary schools of Scottish regarding group work practices (Thurston, Christie, Howe, Tolmie, & Topping, 2008). The previous studies regarding CPD had a positive and significant impact on the quality education of primary schools of Ethiopia (Melesse & Gulie, 2019). These findings also are in support of different researchers like (Feiman-Nemser, Schwille, Carver, & Yusko, 1999).…”
Section: Discussionsupporting
confidence: 68%
“…Another study of Iranian second-grade students found a modest correlation between an index measuring the quality of teachers' secondary schools and their pupils' subsequent performance (Melesse & Gulie, 2019).…”
Section: Performancementioning
confidence: 98%
“…Among the standards required is that quality instruction is a must and that provision of trained and competent human resources is essential. This requires teachers to be qualified to perform their work effectively (Melesse & Gulie, 2019). Fullan (2000) indicated that for curriculum implementation to be effectively done, teachers are the most significant.…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia, teachers in ECDE are expected to be changeoriented and reflective to meet the conditions for quality education provision. This is seen when teachers in classrooms use various interactive approaches to assist each learner in their classroom to realise their education potential (Melesse & Gulie, 2019). UNESCO's (2014) report showed a strong relationship between the professional development of teachers and service delivery.…”
Section: Introductionmentioning
confidence: 99%